Timing of thromboprophylaxis in patients with blunt abdominal solid organ injuries undergoing nonoperative management. Issue 1 (January 2021) - Gaitanidis, Apostolos; Breen, Kerry Ann; Nederpelt, Charlie; Parks, Jonathan; Saillant, Noelle; Kaafarani, Haytham M.A.; Velmahos, George C.; Mendoza, April E.
Abstract : BACKGROUND: Decision making regarding the optimal timing for initiating thromboprophylaxis in patients with blunt abdominal solid organ injuries (BSOIs) remains ill-defined, with no guidelines defining optimal timing. In this study, we aimed to evaluate the relationship of the timing of thromboprophylaxis with thromboembolic and bleeding complications in the setting of BSOIs. METHODS: A retrospective analysis of the Trauma Quality Improvement Program database was performed between 2013 and 2016. All patients with isolated BSOIs (liver, spleen, pancreas, or kidney, Abbreviated Injury Scale score, <3 in other regions) who underwent initial nonoperative management (NOM) were included. Patients were divided into three groups (early, <48 hours; intermediate, 48–72 hours; and late, >72 hours) based on timing of thromboprophylaxis initiation. Primary outcomes were rates of thromboembolism and bleeding after thromboprophylaxis initiation. RESULTS: Of the 25, 118 patients with isolated BSOIs, 3, 223 met the inclusion criteria (age, 38.7 ± 17.3 years; males, 2.082 [64.6%]), among which 1, 832 (56.8%) received early thromboprophylaxis, 703 (21.8%) received intermediate thromboprophylaxis, and 688 (21.4%) received late thromboprophylaxis. Late thromboprophylaxis initiation was independently associated with a higher likelihood of both deep vein thrombosis (odds ratio [OR], 3.15; 95% confidence interval [CI], 1.68–5.91, p < 0.001) and pulmonary embolism (OR, 4.29; 95% CI, 1.95–9.42; p < 0.001). Intermediate thromboprophylaxis initiation was independently associated with a higher likelihood of deep venous thrombosis (OR, 2.38; 95% CI, 1.20–4.74; p = 0.013), but not pulmonary embolism ( p = 0.960) compared with early initiation. Early (but not intermediate) thromboprophylaxis initiation was independently associated with a higher likelihood of bleeding (OR, 2.05; 95% CI, 1.11–2.18; p = 0.023), along with a history of diabetes mellitus, splenic, and high-grade liver injuries. CONCLUSION: Early thromboprophylaxis should be considered in patients with BSOIs undergoing nonoperative management who are at low likelihood of bleeding. An intermediate delay (48–72 hours) of thromboprophylaxis should be considered for patients with diabetes mellitus, splenic injuries, and Grades 3 to 5 liver injuries. LEVEL OF EVIDENCE: Therapeutic, Level IV. Abstract : Supplemental digital content is available in the text.